Transnational crime and the criminal-terrorist nexus synergies and corporate trends - Hesterman, Jennifer L. (Walker Paper, 2005)
Modernized transnational crime is on the rise and threatens our national security like never before. Globalization, technological advances, and anarchy resulting from the end of the Cold War has made transnational crime much easier to perpetrate and has given criminals flexibility to change tactics to evade law enforcement continually. Powers bestowed on federal law-enforcement agencies through the Patriot Act must be upheld to help fight modern organized crime and terrorism in the global environment. Agencies require expanded training on proactive, investigative approaches to stop crime and terrorist acts before they happen, not merely to analyze the outcome, as is the traditional procedure. Government agencies are effectively sharing information at the tactical level. Strategic-level interaction is weak and requires attention. With greater education and training on these issues, the US military could be a powerful force multiplier. This study academically frames the issue, providing policy makers a fresh perspective on existing and emerging threats to use in their future planning and modeling efforts.